Skip to content
New issue

Have a question about this project? Sign up for a free GitHub account to open an issue and contact its maintainers and the community.

By clicking “Sign up for GitHub”, you agree to our terms of service and privacy statement. We’ll occasionally send you account related emails.

Already on GitHub? Sign in to your account

Eq1323 not implies eq2744 #1021

Draft
wants to merge 1 commit into
base: main
Choose a base branch
from
Draft
Show file tree
Hide file tree
Changes from all commits
Commits
File filter

Filter by extension

Filter by extension

Conversations
Failed to load comments.
Loading
Jump to
Jump to file
Failed to load files.
Loading
Diff view
Diff view
16 changes: 7 additions & 9 deletions blueprint/src/chapter/1323.tex
Original file line number Diff line number Diff line change
Expand Up @@ -5,14 +5,12 @@ \chapter{Equation 1323}\label{1323-chapter}
x = y \op (((y \op y) \op x) \op y)
\end{equation}
for all $x,y$. Using the squaring operator $Sy := y \op y$ and the left and right multiplication operators $L_y x := y \op x$ and $R_y x = x \op y$, this law can be written as
$$ L_y R_y L_{Sy} x = x$$
and
$$ R_{Sy} L_y R_y x = x$$
respectively. In particular, this gives a way to construct these magmas:
$$ L_y R_y L_{Sy} x = x.$$
In particular, this gives a way to construct these magmas:

\begin{lemma}[Construction of 1323 magmas]\label{1323-construct} Suppose that $M$ is a magma such that
\begin{lemma}[Construction of 1323 magmas]\label{1323-construct}\leanok\lean{Eq1323.eq1323_if_conditions} Suppose that $M$ is a magma such that
\begin{equation}\label{lr}
L_{Sy} R_{Sy} = 1
R_{Sy} L_{Sy} = 1
\end{equation}
and
\begin{equation}\label{lr-simp}
Expand All @@ -26,8 +24,8 @@ \chapter{Equation 1323}\label{1323-chapter}

So now we would like to construct magmas satisfying \Cref{lr} and \Cref{lr-simp}. We need some bijections:

\begin{lemma}[Bijections]\label{bij}
Let $G$ be a countably infinite abelian group of order $2$. Then there exists a bijection $\phi_a: G \to \Q^\times$ for each $a \in G \backslash \{0\}$ such that
\begin{lemma}[Bijections]\label{bij}\leanok\lean{Eq1323.Ingredients.ϕ}
Let $G$ be a countably infinite abelian torsion group of exponent $2$. Then there exists a bijection $\phi_a: G \to \Q^\times$ for each $a \in G \backslash \{0\}$ such that
$\phi_a(0) = 1$ and $\phi_a(a+b) = -\phi_a(b)$ for all $b \in G$, so in particular $\phi_a(a)=-1$.
\end{lemma}

Expand All @@ -36,7 +34,7 @@ \chapter{Equation 1323}\label{1323-chapter}
\end{proof}


\begin{lemma}[Building a magma]\label{build-magma} Let $G$ be a countably infinite abelian group of order $2$, and let $\phi_a$ be as in the previous lemma. Let $N$ be the set of pairs $(x,a)$ with $x \in \Q^\times$ and $a \in G \backslash \{0\}$, and let $M = G \uplus N$ be the disjoint union of $G$ and $N$. Suppose that we have an operation $\op : M \times M \to M$ obeying the following axioms:
\begin{lemma}[Building a magma]\label{build-magma}\leanok\lean{Eq1323.op}\lean{Eq1323.op_RSy_LSy_eq_Id}\lean{Eq1323.op_Ly_Ry_eq_LSy} Let $G$ be a countably infinite abelian torsion group of exponent $2$, and let $\phi_a$ be as in the previous lemma. Let $N$ be the set of pairs $(x,a)$ with $x \in \Q^\times$ and $a \in G \backslash \{0\}$, and let $M = G \uplus N$ be the disjoint union of $G$ and $N$. Suppose that we have an operation $\op : M \times M \to M$ obeying the following axioms:
\begin{itemize}
\item (i) We have
\begin{equation}\label{op-0}
Expand Down
7 changes: 4 additions & 3 deletions blueprint/src/chapter/infinite_magma_constructions.tex
Original file line number Diff line number Diff line change
Expand Up @@ -781,6 +781,7 @@ \subsection{Second construction}
$$ f(-7)=-4, f(-3) = 4, f(-2)=-3, f(-1)=-1, f(0) = 1, f(1) = 3, f(3)=0, f(4) = -2, f(6) = 2.$$

In this construction, we define a partial solution to be a function $f: E \to \Z$ defined on a finite subset of $E$ obeying the following axioms:
\lean{Eq63.Greedy.PartialSolution}
\begin{itemize}
\item[(i)] $E$ contains $E_0$, and $f$ agrees with $f_0$ on $E_0$.
\item[(ii)] If $h \in E$ and $f(h) \in E$, then $f^2(h)-h$ is also in $E$, and $f(f^2(h)-h) = -h$.
Expand All @@ -796,7 +797,7 @@ \subsection{Second construction}
\begin{proof} Finite check.
\end{proof}

\begin{lemma}[Extension]\label{extension-lemma} If $f: E \to \Z$ is a partial solution and $h_0 \in \Z$, then there exists an extension $f': E' \to \Z$ for which axiom (ii) applies, i.e., $h_0 \in E'$, $f'(h_0) \in E'$, $(f')^2(h_0)-h_0 \in E'$, and $f'((f')^2(h_0)-h_0) = -h_0$.
\begin{lemma}[Extension]\label{extension-lemma}\leanok\lean{Eq63.Greedy.Extension.Next}\lean{Eq63.Greedy.Extension.next} If $f: E \to \Z$ is a partial solution and $h_0 \in \Z$, then there exists an extension $f': E' \to \Z$ for which axiom (ii) applies, i.e., $h_0 \in E'$, $f'(h_0) \in E'$, $(f')^2(h_0)-h_0 \in E'$, and $f'((f')^2(h_0)-h_0) = -h_0$.
\end{lemma}

\begin{proof} We divide into cases.
Expand Down Expand Up @@ -842,10 +843,10 @@ \subsection{Second construction}

Iterating this lemma, we conclude

\begin{corollary}[Greedy completion of Dupont]\label{dupont-iter} Every partial solution $f: E \to \Z$ can be extended to a global solution $f': \Z \to\Z$ of \Cref{dupont-eq}.
\begin{corollary}[Greedy completion of Dupont]\label{dupont-iter}\leanok\lean{Eq63.Greedy.exists_extension} Every partial solution $f: E \to \Z$ can be extended to a global solution $f': \Z \to\Z$ of \Cref{dupont-eq}.
\end{corollary}

\begin{corollary}[Non-injective Dupont solution]\label{non-inject} The Dupont equation admits non-injective solutions, and hence can violate Equation 1692.
\begin{corollary}[Non-injective Dupont solution]\label{non-inject}\leanok\lean{Eq63.Equation63_not_implies_Equation1692} The Dupont equation admits non-injective solutions, and hence can violate Equation 1692.
\end{corollary}

\begin{proof} It suffices to find a partial solution that violates injectivity. This can be done for instance by adjoining $\{-13, 10\}$ to $E_0$ and defining $f(10)= 2 = f(6)$, $f(-13)=-10$, and performing a finite check to verify that this is still a partial solution.
Expand Down
Original file line number Diff line number Diff line change
Expand Up @@ -269,4 +269,13 @@ theorem ne_inv_of_ne_one {x : FreeGroup α} (x_ne_one : x ≠ 1) : x ≠ x⁻¹
rw [← eq]
exact pow_two x

theorem pow_injective {x y : FreeGroup α} {n : ℕ} (hn : n ≠ 0) : x = y ↔ x ^ n = y ^ n := by
sorry

theorem zpow_injective {x y : FreeGroup α} {n : ℤ} (hn : n ≠ 0) : x = y ↔ x ^ n = y ^ n := by
rw [pow_injective (Int.natAbs_ne_zero.mpr hn)]
rcases Int.natAbs_eq n with h | h
· rw [h, Int.natAbs_ofNat, zpow_natCast, zpow_natCast]
· rw [h, Int.natAbs_neg, Int.natAbs_ofNat, zpow_neg, zpow_neg, inv_inj, zpow_natCast, zpow_natCast]

end FreeGroup
44 changes: 44 additions & 0 deletions equational_theories/FreshGenerator.lean
Original file line number Diff line number Diff line change
Expand Up @@ -26,6 +26,12 @@ instance [Nonempty α] : Infinite (FreeGroup α) :=
Infinite.of_injective (FreeGroup.of a ^ ·) <| by
simp [FreeGroup.norm_of_pow, infinite_order]

instance [DecidableEq α] : DecidableEq (FreeGroup α) :=
fun a b =>
if h : a.toWord = b.toWord
then isTrue (FreeGroup.toWord_inj.mp h)
else isFalse (mt FreeGroup.toWord_inj.mpr h)


def generatorNames' : List (α × Bool) → Finset α
| [] => ∅
Expand Down Expand Up @@ -247,4 +253,42 @@ theorem forgetOld_old {S : Finset (FreeGroup α)} {x : FreeGroup α} (hxS : x
apply dropGenerators_generatorNames
exact Finset.subset_biUnion_of_mem _ hxS

noncomputable section

/- This is a simpler version of the above, that only projects into a single dimension - of the
freshGenerator. Calculation with numbers works a bit better with `simp` so this is easier to use
if it's suitable. -/

def projectFresh' (S : Finset (FreeGroup α)) (a : α) : Multiplicative ℤ :=
if a = freshGeneratorName S then (1 : ℤ) else (0 : ℤ)

def projectFresh (S : Finset (FreeGroup α)) : FreeGroup α →* Multiplicative ℤ where
toFun x := FreeGroup.lift (projectFresh' S) x
map_one' := rfl
map_mul' := by intros; simp

@[simp] theorem projectFresh_fresh {S : Finset (FreeGroup α)} : projectFresh S (freshGenerator S) = (1 : ℤ) := by
simp [projectFresh, projectFresh', freshGenerator]

theorem projectFresh_old' {S : Finset (FreeGroup α)} (L : List (α × Bool)) :
generatorNames' L ⊆ S.biUnion generatorNames → projectFresh S (mk L) = 1 := by
induction L
case nil => simp [generatorNames', ← one_eq_mk]
case cons head _ ih =>
rw [← List.singleton_append]
intro hn
simp only [generatorNames', List.singleton_append] at hn
rw [← mul_mk, projectFresh, MonoidHom.map_mul, ← projectFresh, ih]
· have : head.1 ∈ S.biUnion generatorNames :=
Finset.singleton_subset_iff.mp $ Finset.union_subset_left hn
have : freshGeneratorName S ∉ S.biUnion generatorNames := (existsFreshGeneratorName S).choose_spec
simp [projectFresh, projectFresh']
by_cases head.2 <;> aesop
· exact Finset.union_subset_right hn

theorem projectFresh_old {S : Finset (FreeGroup α)} {x} (h : x ∈ S) : projectFresh S x = 1 :=
mk_toWord (x := x) ▸ projectFresh_old' _ fun _ h' ↦ Finset.mem_biUnion.mpr ⟨x, h, h'⟩

end

end FreshGenerator
Loading
Loading